Environmental policy and industrial competitiveness: The pollution haven hypothesis reconsidered - Rolf Bommer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The Pollution-Haven Hypothesis suggests that tight environmental standards reduce domestic producers' competitiveness and give rise to their relocating to countries with more lenient standards. This paper questions that relocation is always caused by reduced competitiveness at home. By using a signaling approach, I show that relocation can be undertaken for purely strategic reasons. Relocation is the producer's tool to convince the policy maker to refrain from a further tightening of environmental control. I show that trade liberalization increases probability of strategic relocation.
Keywords: D78; F13; F15; 330; environmental policy; trade liberalization; industrial competitiveness; international political economy; signaling; Umweltpolitik; Produktionsstandort; Standortwettbewerb; Betriebliche Standortwahl; Handelsliberalisierung; Theorie